테트라메틸사일렌을 이용한 탄화규소 나노로드의 성장 - 노대호; 김재수; 변동진; 양재웅; 김나리 (한국재료학회, 2003)
SiC nanorods have been grown on Si (100) substrate directly. Tetramethylsilane and Ni were used for SiC nanorod growth. After 3minute, SiC nanorod had grown by CVD. Growth regions ware divided by two regions with diameter. The First region consisted of thin SiC nanorods having below 10 nm diameter, but second region's diameter was 10~50 nm. This appearance shows by reduction of growth rate. The effect of temperature and growth time was investigated by scanning electron microscopy. Growth temperature and time affected nanorod's diameter and morphology. With increasing growth time, nanorod's diameter increased because of the deactivation effect. But growth temperatures affected little. By TEM characterization, grown SiC nanorods consisted of the polycrystalline grain.